Role of data as an interface between primary, secondary and tertiary care: Evidence from literature - Giri, Amrit; Ud Din, Fareed (Informatics and Health, 2025)
The healthcare system relies on efficient data flow across primary, secondary, and tertiary care levels to ensure timely and effective patient care. However, despite the growing body of research on data sharing across different healthcare levels, significant gaps remain in understanding the practical implementation of interoperable systems and their long-term impact on patient outcomes and healthcare efficiency. This paper systematically explores the role of data as an interface connecting these different care levels via a systematic literature review. By utilising PRISMA guidelines, this study identifies the current practices and challenges in data sharing and its impact on care coordination. The findings highlight the importance of integrating electronic health records (EHRs) and health information exchange (HIE) platforms in facilitating real-time data sharing, which enhances decision-making and continuity of care, and presents key barriers such as data security, interoperability issues, and the financial burden of implementing data-sharing infrastructure. This study also discusses potential solutions, including standardisation initiatives, policy frameworks, and patient education to improve data sharing across healthcare settings. This study analyses a dataset extracted from online peer-reviewed databases for publications between 2015 and 2024, focusing on data-sharing practices, interoperability challenges, and technological advancements in healthcare systems across primary, secondary, and tertiary care levels. The findings from the final set of selected 26 reference studies, following the standard screening process, reveal that integrated data-sharing systems, supported by standardisation initiatives and robust policy frameworks, can significantly enhance care coordination across primary, secondary, and tertiary levels, leading to reduced redundant medical interventions, improved clinical decision-making accuracy, and a tangible improvement in patient outcomes. This research contributes to the growing body of knowledge advocating for more effective use of data in healthcare, ultimately bridging the gap between various levels of care. •Data as a Critical Interface: Highlighting the pivotal role of data in bridging primary, secondary, and tertiary care levels; enhancing care coordination.•Systematic Literature Review: Employing PRISMA guidelines, to synthesise existing literature on current practices and challenges for information exchange.•Impact of EHR and HIE: Identifies EHRs and HIE platforms as fundamental tools for achieving seamless data flow and continuity of care.•Challenges in Data Sharing: Highlights key barriers, such as interoperability, data security, and financial constraints, as major impediments overall.•Solutions for Optimized Care: Discusses strategies of standardization, regulatory frameworks, and essential patient education for effective data-sharing.